The Influence of Hemoglobin and Motivation on Students' Physical Fitness - Sih Ageng Lumadi; Septi Viantri Kurdaningsih; Wijayantono; Yunita Kristina (CV. Get Press Indonesia, 2025)
This study aims to analyze the effect of hemoglobin levels and motivation on students' physical fitness. This study used a quantitative approach with a correlational design and involved 60 students as respondents who were randomly selected through random sampling techniques. The variables studied consisted of hemoglobin levels measured with a hemoglobinometer, motivation levels measured using a questionnaire with a Likert scale, and physical fitness measured through physical tests which included running 1,600 meters, push-ups, and sit-ups. The results of bivariate analysis showed a significant relationship between hemoglobin levels and students' physical fitness (p = 0.003). In addition, the study also showed a significant relationship between motivation and students' physical fitness (p = 0.001). Students with high motivation had better physical fitness, with most being in the good (18.3%) and moderate (16.7%) categories. The results of this study confirmed that sufficient hemoglobin and high motivation play an important role in supporting students' physical fitness. This study provides important insights into the factors that influence students' physical fitness in an educational setting.